Farmer field schools and local agricultural research committes as complementary platforms - Thiele, Graham; Braun, Ann R.; Gandarillas, Edson (International Development Research Centre, 2004)
Farmer field schools (FFS) and local agricultural research committees (CIALs) are platforms supporting integrated decision-making and innovation for sustainable agriculture. They share several basic principles and processes but their main objectives differ. The first is oriented towards providing agroecological education through participatory learning, whereas the second is a permanent local research service that links farmer experimentation with formal research. This paper compares their objectives, principles and processes as a basis for exploring their application and looks at the new challenges and opportunities.